(3GdehGLgI GdLfGFjI dXGgQI GdEJLGQ HGdHTQ (B: s (3OQGSI ebGQfI (B/ s - (3YdjGA Wg SYjO GdSjOs; (3YeQ eMeO eMeO SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2021)
(3GdEJLGQ HGdHTQ gh EMOi GdXhGgQ GdYGdejI GdJi GfJTQJ GfJTGQG edMhkXG ai GdSfhGJ GdCNjQI(B. (3h ZGdkHG eG jbJQf fTGW Jdc GdXGgQI HGdCReGJ GdfGTFI Yf GdfRGYGJ GdeSdMI Ch GdchGQK GdWHjYjI(B: (3h cPdc ai GdeLJeYGJ GdJi JYGfi ef GdabQ h GdJOghQ GdMGO ai GdNOeGJ GdVQhQjI(B. (3h gh eG jDOi HGdVQhQI dhbhY CYOGO cHjQI ef GdHTQ JMJ NWQ GdGSJZdGd ef bHd YUGHGJ ELQGejI efXeI(B. (3h JJWdH ecGaMI LQGFe GdGJLGQ HGdCTNGU ef GdOhd cGaI HPd eSGYjgG ai GdJYGhf HjfgG decGaMI gPG GdfhY ef GdELQGe(B. (3EP Cnf GQJHGW GdefXeGJ GdELQGejI GdJi JYed ai GdEJLGQ HGdCTNGU eY efXeGJ CNQi JbY NGQL GdMOhO GdEbdjejI ddOhdI jbJVi GdJYGhf Hjf GdOhd ai eLGd JHGOd GdeYdheGJ Mhd Jdc GdefXeGJ(B: (3h GdCfTWI GdeJYdbI HGdEJLGQ HGdCTNGU GdJi JVWdY HgGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2021s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B350-364s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdGJLGQs; (3GdHTQs; (3GdQbs; (3GdCYVGAs; (3GdWads; (3GdGSJZdGd GdLfSjs; (3GdGSJZdGd GdGbJUGOjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs